Transforming Customer Experience through Artificial Intelligence: The Marketers’ Perspective - Vatroslav Škare (Tržište)
Purpose – The emergence of artificial intelligence (AI) created many opportunities for improving and enhancing customer experiences in the digital environment. The aim of this paper is to highlight the main areas of customer experience improvements and enhancements based on the application of artificial intelligence, from a marketers’ perspective. Design/methodology/approach – A literature review was conducted to assess current scientific knowledge on the role of artificial intelligence in improving and enhancing customer experience of digital products and services. Furthermore, as part of exploratory research, in-depth interviews were conducted with marketing experts experienced in digital product/service management. Findings and implications – A range of insights and reflections on the role of artificial intelligence in customer experience improvements and enhancements are provided. Key areas of applicability of artificial intelligence in customer experience improvements and enhancements are identified and discussed, including personalization, service quality, and convenience. Limitations – The findings of this study are constrained by its exploratory nature and the methodology of in-depth interviews with a limited number of key informants, potentially limiting their generalizability. Furthermore, the reliance on qualitative data may introduce subjective biases and overlook quantitative analysis. Originality – This study extends understanding of the role artificial intelligence has in improving and enhancing customer experience in the digital environment. It also provides a managerial perspective on the phenomenon.